Is it time for artificial intelligence to predict the function of natural products based on 2D-structure. Issue 10 (12th June 2019) - Liu, Miaomiao; Karuso, Peter; Feng, Yunjiang; Kellenberger, Esther; Liu, Fei; Wang, Can; Quinn, Ronald J.
Abstract : One of chemistry's grand challenges is to find a function for every known metabolite. We explore the opportunity for artificial intelligence to provide rationale interrogation of metabolites to predict their function. Abstract : Currently, there is no established technique that allows the function of a compound produced by nature to be predicted by looking at its 2-dimensional chemical structure. One of chemistry's grand challenges: to find a function for every known metabolite. We explore the opportunity for Artificial Intelligence to provide rationale interrogation of metabolites to predict their function.